Obesity Discrimination in the Recruitment Process: “You’re Not Hired!” - Flint, Stuart W.; Čadek, Martin; Codreanu, Sonia C.; Ivić, Vanja; Zomer, Colene; Gomoiu, Amalia (Frontiers in Psychology, 2016)
Previous literature reports that obese persons are discriminated in the workplace. Evidence suggests that obese people are perceived as having less leadership potential, and in comparison to normal weight peers, are expected to be less successful. This study examined whether obese people are discriminated against when applying for employment. Three hypotheses were offered in line with previous research: 1) obese people are less likely to be assessed positively on personnel suitability than normal weight people; 2) obese people in active employment are more likely to be discriminated against than people in non-active employment; and 3) obese women are more likely to be discriminated against than obese men. 181 Participants were sampled from sedentary, standing, manual and heavy manual occupations. Participants rated hypothetical candidates on their suitability for employment. Employees also completed measures of implicit and explicit attitudes towards obesity. MANOVA was conducted to examine if obese candidates were discriminated against during the recruitment procedure. Results demonstrated that participants rated obese candidates as less suitable compared with normal weight candidates and when the weight status of the candidate was not revealed for work across the four workplace groups. Participant gender and weight status also impacted perceptions of candidates’ suitability for work and discrimination towards obese candidates was higher in participants from more physically demanding occupations. The study findings contribute to evidence that obese people are discriminated against in the hiring process and support calls for policy development.